Clinical characteristics associated with increased wound size in patients with recessive dystrophic epidermolysis bullosa. Issue 3 (21st March 2021) - Solis, Daniel C.; Gorell, Emily S.; Teng, Claudia; Barriga, Melissa; Nazaroff, Jaron; Li, Shufeng; Subica, Andrew; Lu, Ying; Marinkovich, M. Peter; Tang, Jean Y.
Abstract: As more therapeutic clinical trials focus on treatment of individual wounds in patients with recessive dystrophic epidermolysis bullosa, it has become crucial to understand the baseline clinical characteristics of these wounds. To investigate these features, we administered an RDEB‐specific wound survey. Forty participants reported on location, size, pain, infection frequency, wound type, and duration of 189 wounds; a subset of 22 participants reported on pruritus in 63 wounds. Increased wound size was significantly associated with increased pain, increased pruritus, longer wound duration, increased infection frequency, and patients with mutations resulting in truncated type VII collagen.